2023
DOI: 10.1371/journal.pone.0285088
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intake and metabolic parameters of Japanese university students with and without obesity: Sex-specific differences

Abstract: Objective To establish effective methods of obesity prevention among young adults, we analyzed the relationship between obesity-related food intake and metabolic factors in Japanese university students. Methods We performed a cross-sectional analysis of nutrient intake information and metabolic parameters among 1,206 Gifu University students categorized by body mass index. Results The overweight/obesity rate was significantly higher in males. Additionally, among males, the intake of protein, potassium, mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In contrast with most of the findings, Mehta et al [ 68 ] identified a higher magnesium intake in males with obesity (mean daily intake of 254.9 ± 101.1 mg/day) compared with normal-weight men (mean intake of 242 ± 102.2 mg/day). In women, however, the difference was not statistically significant [ 68 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast with most of the findings, Mehta et al [ 68 ] identified a higher magnesium intake in males with obesity (mean daily intake of 254.9 ± 101.1 mg/day) compared with normal-weight men (mean intake of 242 ± 102.2 mg/day). In women, however, the difference was not statistically significant [ 68 ].…”
Section: Discussionmentioning
confidence: 77%
“…In contrast with most of the findings, Mehta et al [ 68 ] identified a higher magnesium intake in males with obesity (mean daily intake of 254.9 ± 101.1 mg/day) compared with normal-weight men (mean intake of 242 ± 102.2 mg/day). In women, however, the difference was not statistically significant [ 68 ]. Similarly, Liu et al [ 69 ] did not confirm any differences in terms of daily magnesium intake according to the obesity status, neither in Non-Hispanic Black people nor in Mexican American people aged between 19 and 39 years (this was a NHANES sub-analysis, between 2003 and 2014) [ 69 ].…”
Section: Discussionmentioning
confidence: 77%